Improvement in the Quality of Early Postoperative Course After Endoscopic Transsphenoidal Pituitary Surgery: Description of Surgical Technique and Outcome - Pan, Xinfa; Ma, Yuehui; Fang, Minwei; Jiang, Jiajing; Shen, Jie; Zhan, Renya (Frontiers in Neurology, 2020)
Objective: The endoscopic transsphenoidal pituitary surgery has gained popularity, and has shown excellent results with a more comfortable postoperative course. However, the quality of early postoperative course is not well established in endoscopic transsphenoidal pituitary surgery. We hypothesized that the quality of early postoperative course would be improved when implemented an enhanced recovery after surgery (ERAS) protocol and minimally invasive endoscopic transsphenoidal pituitary surgery. Methods: We implemented a perioperative management ERAS protocol for endoscopic transsphenoidal pituitary surgery by an experienced surgeon (Yuehui Ma) in our department from January 2018. And from then the endoscopic transsphenoidal pituitary surgery was implemented with minimally invasive technique, such as bonely sella reconstruction and partially nasal packing. We compared the results of 78 endoscopic transsphenoidal pituitary surgery cases during the initiation of ERAS protocol and minimally invasive technique implementation: 37 cases in control group and 41 cases in ERAS group. Outcomes assessed included the effectiveness and security of surgery, postoperative hospital length of stay (LOS), and postoperative status on postoperative day 1 (POD1). Results: Postoperative status on POD1, such as nasal ventilation, out of bed, headache score, liquid supplement had significant improvement (P<.05). The median postoperative LOS decreased from 8 days in control group to 3 days in ERAS group (P<.05). ERAS group had better economic benefit with less Hospital charges (P<.05). There was no difference in the early postoperative diabetes insipidus and 30-day readmission for epistaxis, hyponatremia, or other complications between the two groups. Conclusion: The quality of early postoperative course was improved when implemented a neurosurgical ERAS protocol and minimally invasive endoscopic transsphenoidal pituitary surgery with partially nasal packing. Endoscopic transsphenoidal pituitary day surgery could be recommended in some classes of patients, though further evaluation in large cases studies is warranted.